2022
DOI: 10.1097/meg.0000000000002436
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of ustekinumab in elderly Crohn’s disease patients

Abstract: Objective Anti-tumour necrosis factor (TNF) agents are associated with increased infection risk among elderly IBD patients, but little is known about non anti-TNF biologics in this cohort. We examined the safety and effectiveness of ustekinumab in elderly Crohn’s patients. Methods This retrospective multi-centre cohort study included Crohn’s patients ≥60-years old who commenced ustekinumab. We recorded Harvey-Bradshaw index (HBI), concomitant steroid therapy, treatment persistence and new infections or malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…However, a proportion of patients still show poor responses on the already q8w and q4w drug intervals, which calls for intravenous reinduction as a rescue treatment. To date, published studies evaluating the efficacy and safety of extra weight-based intravenous doses of UST are scarce ( 24 , 25 ). A recent study including 65 patients has demonstrated that 31% of patients achieved clinical remission off corticosteroids after UST intravenous reinduction ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data are expressed as percentages according to different outcomes. SFR = steroid-free remission, SFP = steroid-free persistence, FU = follow-up, MH = mucosal healing, naïve: Patients without prior biologic treatment, studies including a younger control group of patients treated with the same biologic drug are represented with parallel bars, studies comparing different therapeutic drugs are allocated to the respective column, Ref [ 36 ] was excluded because only treatment failure was calculated [ 30 , 31 , 32 , 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Anti-tumor Necrosis Factor (Tnf) Agentsmentioning
confidence: 99%
“…Effectiveness : In the first report on 70 elderly CD with a mean CCI of 4.14, USTE showed a good effectiveness and safety profile with a median treatment of 16 months. More than half of these patients were anti-TNF and/or VEDO experienced [ 45 ]. Another study comparing a small cohort of older CD patients compared with younger patients found a lower probability of achieving steroid-free remission in patients ≥65-years-old [ 46 ].…”
Section: Ustekinumabmentioning
confidence: 99%